Ash aggregation in explosive volcanic eruptions. Issue 10 (29th May 2013) - Telling, J.; Dufek, J.; Shaikh, A.
Abstract : [1] Eruption dynamics are sensitive to ash aggregation, and aggregates are commonly found in eruptive deposits. While ash dispersal and associated hazards are sensitive to aggregation, few experiments have been conducted on this phenomena using natural materials across the diverse range of conditions expected in volcanic flows. We have isolated two regimes, wet and dry, in which aggregation occurs due to two different forces, electrostatic and hydrodynamic. Using a closed chamber to create a controlled atmosphere, we found that relative humidity, residence time, and kinetic energy are the three variables necessary to define wet and dry flow regimes. A series of process‐based equations defining the behavior of ash particles have been developed. We propose an aggregation model that can be used for ash dispersal forecasts across a range of conditions in an eruptive plume. Key Points: Ash aggregation is important for eruption dynamics and ash dispersal hazards Two flow regimes, wet and dry, are quantified in ash interactions Experimentally derived expressions describe the physics of ash aggregation